Creation: discovering a hybrid path (Revista Apotheke, 2020)
The research was developed from the use of the body through playful experiences in dialogue with the plastic production of the proposing artist, integrating a personal poetics and a pedagogical experience in Visual Arts. The works produced during this process caused a concern that instigated the research on: artistic creation, body as a support, aesthetic experience, exploration of materials and collective production. In the pedagogical line, the intention was to create strategies that led participants to explore the universe of art, expanding their artistic knowledge through the P.E.R.A Method, Yoshiura (1982). In the artistic line there was the search for a poetic singularity that, in a very subtle way, already brought the union of techniques and supports, configuring itself as an Interformative Hybridization, Valente (2008). This process resulted in the Desplante and Azuis series.
Keywords: creation process; collective creation; visual arts